Application of Wireless Contralateral Routing of Signal Technology in Unilateral Cochlear Implant Users with Bilateral Profound Hearing Loss - Snapp, Hillary A; Hoffer, Michael E; Spahr, Anthony; Rajguru, Suhrud (Journal of the American Academy of Audiology, 2019)
The aim of the study was to determine if contralateral routing of signal (CROS) technology results in improved hearing outcomes in unilateral cochlear implant (CI) patients and provides similar gains in speech perception in noise to traditional monaural listeners (MLs). The study is a prospective, within-subject repeated-measures experiment. Adult, English-speaking patients with bilateral severe-profound sensorineural hearing loss using an Advanced Bionics CI (n = 12) in one ear were enrolled for the study. Hearing performance in the monaural listening condition (CI only) was compared with the CROS-aided (unilateral CI + CROS) condition. Participants were tested for speech-in-noise performance using the Bamford-Kowal-Bench Speech-in-Noise™ test materials in the speech front/noise front (0 degrees/0 degrees azimuth), speech front/noise back (0 degrees/180 degrees azimuth), speech deaf ear/noise monaural ear (90 degrees/270 degrees azimuth), and speech monaural ear/noise deaf ear (90 degrees/270 degrees azimuth) configurations. Localization error was assessed using three custom stimuli consisting of 1/3 octave narrowband noises centered at 500 and 4000 Hz and a broadband speech stimulus. Localization stimuli were presented at random in the front hemifield by 19 speakers spatially separated by 10 degrees. Outcomes were compared with a previously described group of traditional MLs in the CROS-aided condition (normal hearing ear + CROS). All participants were tested acutely with no adaptation to the CROS device. Statistical analyses were performed using Wilcoxon signed rank tests for nonparametric data and paired sample. Statistical significance was set to p < 0.00625 after Bonferroni adjustment for eight tests. Significant benefit was observed from unaided to the CI + CROS-aided condition for listening in noise across most listening conditions with the greatest benefit observed in the speech deaf ear/noise monaural ear (90 degrees/270 degrees azimuth) condition (p < 0.0005). When compared with traditional MLs, no significant difference in decibel gain from the unaided to CROS-aided conditions was observed between participant groups. There was no improvement in localization ability in the CROS-aided condition for either participant group and no significant difference in performance between traditional MLs and unilateral CI listeners. These findings support that unilateral CI users are capable of achieving similar gains in speech perception to that of traditional MLs with wireless CROS. These results indicate that the use of wireless CROS stimulation in unilateral CI recipients provides increased benefit and an additional rehabilitative option for this population when bilateral implantation is not possible. The results suggest that noninvasive CROS solutions can successfully rehabilitate certain monaural listening deficits, provide improved hearing outcomes, and expand the reach of treatment in this population.